The Armadillo BTB Protein ABAP1 Is a Crucial Player in DNA Replication and Transcription of Nematode-Induced Galls - Cabral, Danila; Forero Ballesteros, Helkin; de Melo, Bruno Paes; Lourenço-Tessutti, Isabela Tristan; Simões de Siqueira, Kércya Maria; Obicci, Luciana; Grossi-de-Sa, Maria Fatima; Hemerly, Adriana S.; de Almeida Engler, Janice (Frontiers in Plant Science, 2021)
The biogenesis of root-knot nematode (Meloidogyne spp.) induced galls requires the hyperactivation of the cell cycle with controlled balance of mitotic and endocycle programs to keep its homeostasis. To better understand gall functioning and to develop new control-strategies for this pest, it is essential to find out how the plant host cell cycle programs are responding and integrated during the nematode-induced gall formation. This work investigated the spatial localization of a number of gene transcripts involved in the pre-replication complex during DNA replication in galls and report their akin colocation with the cell cycle S-phase regulator Armadillo BTB Arabidopsis Protein 1 (ABAP1). ABAP1 is a negative regulator of pre-replication complex controlling DNA replication of genes involved in control of cell division and proliferation, therefore its function has been investigated during gall ontogenesis. Functional analysis was performed upon ABAP1 knockdown and overexpression in Arabidopsis thaliana. We detected ABAP1 promoter activity and localized ABAP1 protein in galls during development, and its enhanced expression displayed significantly reduced gall sizes containing atypical giant cells. Profuse ABAP1 expression also impaired gall induction and hindered nematode reproduction. Remarkably, ABAP1 knockdown likewise negatively affected gall and nematode development suggesting its involvement in the feeding site homeostasis. Microscopy analysis of cleared and nuclei stained whole-galls revealed that ABAP1 accumulation resulted in aberrant giant cells displaying interconnected nuclei filled with enlarged heterochromatic regions. As well, imbalanced ABAP1 expression caused changes in expression patterns of genes involved in the cell division control as investigated by qPCR. CDT1a, CDK1 and E2Fa levels were significantly decreased in galls upon ABAP1 overexpression possibly contributing to the structural changes in galls during nematode infection. Overall, data obtained in galls reinforced the role of ABAP1 controlling DNA-replication and mitosis, and consequently cell proliferation. ABAP1 expression might likely take part of a highly ordered mechanism of cell cycle control balance preventing gall expansion. Our data strongly suggest that ABAP1 as a unique plant gene is an essential component for cell cycle regulation throughout gall development during nematode infection and is required for feeding site homeostasis. ABAP1 expression might prevent galls to expand limiting further mitotic activity.